Hening, 4 Statutes at Large ch. 4 sec. 14 at 131 (1823) - (:unkn) unknown (My University, 1723)
"And be it further enacted, by the authority aforesaid, That no negro, mulatto,or Indian whatsoewver; (except as is hereafter excepted,) shall hereafter presume to keep, or carry any gun, powder, shot, any club, or other weapon whatsoever, offensive or defensive; but that every gun, and all powder and shot,whipped. and every such club or weapon. as aforesaid, found or taken in the hands, custody, or possession of any such negro, mulatto, or Indian, shall be taken away..."
Keywords: ENSLAVED PERSONS & OTHER MINORITIES